UPAYA MENINGKATKAN KEAKTIFAN BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN THINK PAIR SHARE SISWA KELAS VIID SMP N 1 SRUMBUNG KABUPATEN MAGELANG - Fibriana Ayukmartina; A. A Sujadi; Agustina Sri Purnami (Universitas Sarjanawiyata Tamansiswa, 2014)
The purposes of this study was to improve liveliness and mathematics achievement students VIID in junior high school 1 Srumbung Magelang with cooperative learning TPS (Think Pair Share). This research is Classroom Action Research (CAR). The subjects in this study were students of class VII D which is 34 students who comprised 18 male students and 16 female students. The objects of this research are being active and increase math Â achievement. It is shown by an increase in the average yield percentage of being activeÂ student learning Â based on the observation sheet. The first cycle was 53,91% became 75,97% in cycle II.